Hubungan antara Kontrol Diri dengan Prokrastinasi dalam Menyelesaikan Skripsi pada Mahasiswa Universitas Muria Kudus - Aliya Noor Aini; Iranita Hervi Mahardayani (Universitas Muria Kudus, 2011)
This study aims to examine the relationship between self-control with procrastination in finishing the final project on college students. Inthis study the subjects of research is the student at Universitas Muria Kudus, with a purposive sampling. That is based on a characteristics arestudents at the Universitas Muria Kudus who already took a final project at least two semesters and take the achieve study periodmore than 8 semesters. Results of analysis of data obtained from both the correlation coefficient rxy = 0.401 with a p = 0.000 (p smaller than 0.01) this means there is a very significant negative relationship between self-control with procrastination in completing the final project on student at Universitas Muria Kudus. Effective contribution of self-controlvariables on procrastination in finishing the final project are 16.08%.